Genetic variability, heritability and character association studies in sweet corn (Zea mays L. saccharata) - M.S. Niji; R.Ravikesavan; K.N.Ganesan and; T.Chitdeshwari (Electronic Journal of Plant Breeding, 2018)
An investigation was carried out in sweet corn to evaluate seven lines, seven testers and their 49 crosses during Kharif 2017. The study revealed highly significant differences among genotypes, indicating the presence of substantial genetic variability. High heritability coupled with high genetic advance as percent of mean was recorded for the traits viz., green cob yield, green cob weight, 100 seed weight, total sugar, reducing sugar, non-reducing sugar, iron content and zinc content, indicated the importance of these traits for selection. Correlation studies revealed significant positive association of green cob yield with green cob weight, cob breadth, tassel length, plant height, cob length, total chlorophyll content, tassel branches, cob placement height, 100 seed weight and number of kernel rows per cob. Non-significant association between green cob yield and total sugar content indicated the possibility of simultaneous improvement of these traits through further breeding programmes.